2015
DOI: 10.1038/gim.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of New York children with sickle cell disease identified through newborn screening

Abstract: Purpose Long-term follow-up of newborn screening for conditions such as sickle cell disease can be conducted using linkages to population-based data. We sought to estimate childhood sickle cell disease mortality and risk factors among a statewide birth cohort with sickle cell disease identified through newborn screening. Methods Children with sickle cell disease identified by newborn screening and born to New York residents in 2000–2008 were matched to birth and death certificates. Mortality rates were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The deaths of the other five children with Hb SC were not related to the pathology in question. Another interesting finding of this research was that SCD was mentioned on the death certificate in only 57% of the cases ( n  = 12) 34 . A recent study in the USA about the mortality rate of children and adults with SCD showed a decrease in the first group (3%) and an increase in the second (1%) during the same period of 26 years (1979–2005) 35 .…”
Section: Discussionmentioning
confidence: 61%
“…The deaths of the other five children with Hb SC were not related to the pathology in question. Another interesting finding of this research was that SCD was mentioned on the death certificate in only 57% of the cases ( n  = 12) 34 . A recent study in the USA about the mortality rate of children and adults with SCD showed a decrease in the first group (3%) and an increase in the second (1%) during the same period of 26 years (1979–2005) 35 .…”
Section: Discussionmentioning
confidence: 61%
“…Although there are no data from Africa, reports from the US, United Kingdom, and Jamaica demonstrate the survival benefits for children with SCA identified by NBS, although it is difficult to extract the specific benefits of NBS, preventive care, and acute clinical care. 5-8,28,29 Our model indicates that NBS and simple preventive treatments are highly cost-effective across all scenarios, regardless of which mortality assumptions or datasets were used. Compared with the US, the incremental cost-effectiveness ratios are greater for NBS in Angola.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, overall mortality rate for all patients was 0.23/100 person-years during the first five years of life and overall probability of survival was of 98.9%. Although the rate of death between 1-4 years of age remained higher than in the French general population for this age-group during the same period (0.19 versus 0.03/100), [12] these results align with a recent UK national study [8] that showed a reduced mortality in children under five (death rate of 0.17/100 person-years of follow-up for all sickle cell disorders and 0.26 per 100 person-years in homozygous children) or older reports from pediatric cohorts in similar high-income settings (Dallas cohort, 1983-2007, 0.52/100 patient-years [6], New York, 2000-2008, 0.38/100 person-years in the first two years of life) [13], East London , no deaths at five years) [5] or regional French cohorts (0.25 and 0.32/100 patient-years, respectively in North East Paris area and Créteil) [4,7]. Arguably, our study differs by focusing on the first five years of life only, but in SCD these are the most vulnerable years, along with young adulthood when a second peak of mortality occurs after transitioning [14].…”
Section: Discussionmentioning
confidence: 99%